Exploring Fintech Organizational Culture: Are they unique? - Anita Maharani; Valensius Alvin Mulia; Cut Azyya Triatsari (BASKARA : Journal of Business and Entrepreneurship, 2022)
The purpose of this study is to discover the nature of organisational culture in startup enterprises involved in finance technology. The study will be useful since it may be used as an example or description of organisational culture in Indonesia. Academically, there is a startup organisational culture model that complements the current organisational culture paradigm. Organizational culture is the primary theory presented in this research. The research method used in this study is qualitative, and the respondents are four principals of financial technology start-up companies in Indonesia. We use the Analytical Hierirchal Process to analyse data (AHP).